Advances in Applied Ceramics: Guest editorial - Hazell, Paul J. (Maney Publishing, 2010)
The development, engineering, and testing of ceramic armour systems and materials has been carried out during the past 50 years and dates back to the pioneering work of M. L. Wilkins and his colleagues [1]. Arguably, the first indications that such armour would be ballistically efficient were seen much earlier than Wilkins when, in 1918 Maj Neville Monroe‐Hopkins found that a thin layer of enamel improved the ballistic performance of a thin steel plate [2]. Indeed, many early designs employed a hard ceramic face backed by a relatively ductile material, thereby employing the disruptor (or ‘disturber’)/absorber recipe that is still used in modern armour systems today.
Keywords: ceramic armour; orgins of ceramic armour; advances in ceramic armour.